The Impact of Southern African Customs Union on Botswana’s External Trade - Molefhe, Lone (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
The aim of the study was to analyse the impact of a regional agreement South African Customs Union (SACU) on a member state, Botswana’s external trade. As one of the oldest trade agreements in the world SACU agreement renewed in 2002, where the members other than South Africa, Botswana, Lesotho, Namibia and Eswatini, in order to benefit more from the union. Study focused on the period 2002-2021, both due to analyse the impact of new amended agreement as well as the availability of data. In order to test the impact of Customs Union on Botswana’s trade Gravity Model is used. Beside the model’s major variables as total trade value, real GDP and distance, real exchange rate is added as an independent variable and membership to SACU, border country status and common language added as dummy variables to the model. For the sample of the model 22 countries selected consisting of major trade partners of Botswana. Panel regression is used to estimate the impacts of independent variables total GDP, geographic distance and real exchange rate and dummy variables as union membership to SACU, common border with Botswana and common language variables are used. Sample of the study selected as the 22 major trading partners of Botswana. Regression results as expected shows that as the GDPs of partner countries is increasing, it influences the trade volume positively. On the other hand, as the geographical distance increases between trade partners volume of trade negatively affected, similarly any deterioration in exchange rates influence the trade between partners negatively. Bilateral trade among trading partner countries is affected when Botswana’s currency Pula depreciated or appreciated against the partner country’s currency. Magnitude of effect may change in every partner country depending on the elasticity of demand for imports or supply of exports however that was beyond the aim of this study. For the union membership and having common border among the partners have given a positive sign as expected however results are not found statistically significant.

ÖZ: Bu tezin amacı bölgesel bir ticaret antlaşması olan Güney Afrika Gümrük Birliği’nin (SACU) üyesi bir ülke olan Botswana dış ticaretine etkisini ölçmektir. Dünyadaki en eski ticaret antlaşmalarından olan Güney Afrika Gümrük Birliği 2002 yılında Güney Afrika dışındaki üyeler Botswana, Namibya, Lesotho ve Eswatini’nin de daha etkin faydalanması amacıyla yenilenmişti. Çalışma hem düzenlenen antlaşmanın etkilerini analiz edebilmek hem de veri bulunurluğundan dolayı 2002-2021 dönemlerini kapsamaktadır. Yenilenen antlaşmanın Botswana dış ticareti üzerindeki etkileri analiz etmek için Gravity Model yaklaşımı kullanılmıştır. Modelin temel değişkenleri olarak bağımlı değişken olarak İkili Toplam Ticaret (değer olarak), bağımsız değişken olarak Toplam GSYH, coğrafi uzaklık yanında Reel Döviz kuru, kukla değişken olarak ta SACU üyeliği, komşu ülke konumu ile ortak dil kullanılmıştır. Çalışmanın örneklemi için Botswana’nın önemli ticari ortakları olan 22 ülke seçilerek oluşturulmuştur. Regresyon analiz sonuçları beklendiği gibi ticaret ortaklarının GSYH büyüklükleri arttıkça ticaret hacminin arttığını, coğrafik mesafe arttıkça ticaret hacminin azaldığını göstermiştir. Ayni şekilde kurdaki değer kaybının da ticareti olumsuz etkilediği sonuçlarına ulaşılmıştır. Botswana’nın para birimi Pula’nın ticaret partneri ülke para birimlerine karşı değer kaybetmesi durumunda ikili ticaretin olumsuz etkilendiği görülmektedir. Bu değişimin büyüklüğü ithalata olan talep esnekliği ve ihracatın arz esnekliğine bağlı değişebilmektedir ancak bu unsurlar çalışmanın kapsamı dışındadır. Gümrük Birliği üyeliği etkisini ve ortak dil kullanımını ölçen katsayılar pozitif olmasına rağmen istatistiki olarak anlamlı çıkmamıştırlar.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2023. Supervisor: Asst. Prof. Dr. Yenal Süreç.
Keywords: Thesis Tez; Economics Department; Trade--South African Customs Union (SACU)--Botswana; Economic Conditions and Development--Economic Policy--Trade--South African Customs Union (SACU)--Botswana; SACU; Customs Union; Economic Integration; Gravity Equation; Botswana; Trade Agreements